The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ijheatmasstransfer.2020.119551
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase flow morphology and local wall temperatures in high-aspect-ratio manifold microchannels

Abstract: Manifold microchannel heat sinks can dissipate high heat fluxes at moderate pressure drops, especially during two-phase operation. High-aspect-ratio microchannels afford a large enhancement in heat transfer area; however, the flow morphology in manifold microchannels during two-phase operation, as well as the resulting thermal performance, are not well understood. In this work, a single manifold microchannel representing a repeating unit in a heat sink is fabricated in silicon with a bonded glass viewing windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It goes without saying that more studies are needed so that a better knowledge of phase inversion can be gained. Recently most of the work focussed on the novel detection or physical challenges of pure phases (Agarwal & Dondapati, 2020;Drummond et al, 2020;Li et al, 2020;O'Donovan & Grimes, 2020;Rafałko et al, 2020;Shi et al, 2020) but no research were done on dispersed or emulsified phases.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…It goes without saying that more studies are needed so that a better knowledge of phase inversion can be gained. Recently most of the work focussed on the novel detection or physical challenges of pure phases (Agarwal & Dondapati, 2020;Drummond et al, 2020;Li et al, 2020;O'Donovan & Grimes, 2020;Rafałko et al, 2020;Shi et al, 2020) but no research were done on dispersed or emulsified phases.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…The results show that the manifold structure improves the performance of the single-phase flow rectangular microchannel radiator. Drummond et al [5][6][7] designed and manufactured a silicon-based rectangular manifold microchannel radiator. The microchannel and manifold dividing plate were etched on silicon wafers respectively and bonded together, and a heating circuit simulating electronic chip heating was integrated into the other side of the silicon-based manifold microchannel.…”
Section: Introductionmentioning
confidence: 99%
“…Their result showed that compared to the usual MMHS, the best heat sink could decrease thermal resistance by 19.15% and reduce pressure drop by 1.91% at Re = 295. Drummond et al [27] experimentally studied two-phase flow morphology in high aspect ratio manifold microchannels. Their results showed that for manifold microchannels, the two-phase flow regime plays an important role in heat transfer improvement and must be with accuracy considered in heat sink design.…”
Section: Introductionmentioning
confidence: 99%